Dissolved gas analysis caused by electrical breakdown of liquid impregnated pressboards - Pattanadech, Norasage; Luk-In, Kanchanaporn; Samerpak, Chantapapa; Chumninuan, Nattakrit; Piyapatamin, Nadpakul; Hengcharoensuk, Tassana; Nupinit, Thanapon; Siriworachanyadee, Jompatara (My University, 2019)
The aim of this paper is to analyze the dissolved gases in dielectric liquid caused by electrical breakdown of liquid-impregnated pressboards. The pressboards were prepared with dimension of 100 x 100 x 3.2 mm (W x L x H). First of all, each liquid insulation, mineral oil and natural ester (FR3), was heated at 60°C with 200 mbar for 12 hours. Second, pressboards were heated at 80°C with 200 mbar for 12 hours. Then the heated pressboards were impregnated with the dielectric liquid at 60°C with 200 mbar for 12 hours. The impregnated pressboards were divided into three groups. The first group was tested with AC voltage. The second and third group was tested with positive and negative lightning impulse voltages respectively. From the test results, the type and quantity of generated gases caused by breakdown phenomena is dependent on the type and the number of breakdowns.
Keywords: Dissolved gas analysis; Gas generate; Impregnated pressboard; Mineral oil; Natural ester